Application of SPME‐GC‐TOFMS, E‐nose, and sensory evaluation to investigate the flavor characteristics of Chinese Yunnan coffee at three different conditions (beans, ground powder, and brewed coffee). (29th June 2020) - Cui, Dan Dan; Liu, Yuan; Chen, Yan Ping; Feng, Xi; Lu, Yu; Yu, Bo
Abstract: SPME‐GC‐TOFMS, E‐nose, and sensory evaluation were used to explore the volatile organic compounds (VOCs) in four Chinese Yunnan coffee at three conditions (beans, ground powder, and brewed coffee). VOCs were detected by GC‐TOFMS and compared the difference between all samples, depending on the VOCs in the coffee sample. The E‐nose was used for rapid detection to differentiate the sample. The two results are analyzed by principal component analysis (PCA). Quantitative description analysis (QDA) was used to evaluate the flavor profiles of coffee samples. The results shown that GC‐TOFMS detected 412, 498, and 294 VOCs in roasted, ground powder, and brewed coffee, respectively. The PCA of SPME‐GC‐TOFMS results shown that Nankang coffee was mainly related to ketone compounds; the aroma of Hongguang coffee was determined by dimethyl disulfide and acetic acid; pyrazine and ketone compounds were important to Hainan coffee; ketone and ester compounds were dominated in Xinghuan coffee. The results of E‐nose shown that the first two principal components (PCs) accounted for 97.3%, 92.5%, and 93.8% of variances in roasted, ground powder, and brewed coffee, respectively. The different brands of coffee samples at the same condition shown separated locations on the PCA results of E‐nose. Sensory evaluation shown the special flavor of coffee samples, Nankang coffee with a bake flavor, Hongguang coffee had chocolate and nutty flavors, Hainan coffee had the caramel‐like aroma, and the aroma Xinghuan coffee was sweet. This study could provide a better understanding of Chinese coffee produced in Yunnan province. Abstract : Detection and analysis the flavor characteristics of Chinese Yunnan coffee.